1984
DOI: 10.1038/307272a0
|View full text |Cite
|
Sign up to set email alerts
|

Specific depletion of immunoreactive growth hormone-releasing factor by monosodium glutamate in rat median eminence

Abstract: A potent and specific growth hormone-releasing factor (GRF) was recently isolated and characterized from a human islet cell tumour of the pancreas that caused acromegaly. Antibodies raised against the synthetic replicate of this peptide have allowed the immunohistochemical identification of GRF-producing neurones within the primate central nervous system. Such neurones are found mainly in the arcuate nucleus in human and monkey hypothalamus, suggesting that this nucleus is a primary source of GRF. We have furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
58
0
5

Year Published

1985
1985
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(68 citation statements)
references
References 15 publications
5
58
0
5
Order By: Relevance
“…However, some caution is necessary in interpreting the data obtained following MSG treatment. In particular, it should be noted that, although neonatal MSG treatment destroys the majority of the arcuate GH-releasing hormone neurons, this ablation is not selective, with 70 -90% of all neuronal perikarya in the arcuate nuclei being destroyed (1,5). Thus, MSG treatment may also influence adiposity via the disruption of additional hypothalamic pathways, including those regulating orexigenesis and energy homeostasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some caution is necessary in interpreting the data obtained following MSG treatment. In particular, it should be noted that, although neonatal MSG treatment destroys the majority of the arcuate GH-releasing hormone neurons, this ablation is not selective, with 70 -90% of all neuronal perikarya in the arcuate nuclei being destroyed (1,5). Thus, MSG treatment may also influence adiposity via the disruption of additional hypothalamic pathways, including those regulating orexigenesis and energy homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Homozygous dw/dw rats bred on an Albino Swiss (AS) background, used in studies 3,5,6, and 8, were housed in the Division of Biological Services, National Institute of Medical Research (NIMR; London, UK), under conditions of 12:12-h light-dark (lights on at 0600), with food and water available ad libitum. The hemizygous Tgr rats, wild-type (WT; AS) littermates, and homozygous dw/dw rats used in studies 1, 2, and 7 were derived from the original colonies at NIMR and were bred in the Transgenic Unit (School of Biosciences, Cardiff University) under conditions of 14:10-h light-dark (lights on at 0500), with food and water available ad libitum.…”
Section: Animalsmentioning
confidence: 99%
“…Injecting MSG 4 mg/g body weight s.c. at neonatal age, is known to deplete the arcuate nucleus of GHRH neurons (Bloch et al, 1984) thus leading to GH deficiency. Also, our group had previous experience with this model when investigating the growth process in GH deficient animals (Hermanussen et al, 1996).…”
Section: Animal Datamentioning
confidence: 99%
“…Bloch et al (1984) showed that MSG treatment results in the complete loss of growth hormone releasing factor (GRF)-immunoreactive cell bodies within this nucleus and provokes a selective disappearance of GRF-immunoreactive fibres in the median eminence of rats. This technique has routinely been practised to produce functionally hypopituitary animals (Lima et al, 1993) for studies of short-term growth (Hermanussen et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, although the present data is in keeping with our previous in vitro results (4) showing a direct GLU-SRIF interaction, we cannot totally exclude the involvement of intermediary steps in vivo particularly since GLU participates in a wide variety of metabolic processes. Growth hormone-releasing factor mediation could be a good candidate since this peptide originates in the arcuate nucleus (27) where an intricate interplay of SRIF/ growth hormone-releasing factor could explain the decreased output of hypothalamic growth hormone-releasing factor concomitant with the increased release of SRIF that has been observed (review in 24).…”
Section: Discussionmentioning
confidence: 99%